ISLAM WASTHIYYAH DALAM KACA MATA TAFSIR AL-QUR’AN: (Kajian Teks, Konteks, dan Kontekstualisasi Penafsiran Dalam Q.S. Al-Baqarah: 143) - Arif Sugitanata (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2020)
This paper tries to discuss the concept of Wasthiyyah Islam in the perspective of the Qur'an through various interpretations. Specifically, there are several aspects that became the focal point of this study, First, looking back at the concept of Islamic Wasthiyyah in the Qur'an. Second, revealing the context and nature of Islam Wasthiyyah in a variety of interpretations. Third, to actualize the characteristics of Wasthiyyah Islam in the current context. The research approach used is the study literature approach which is based on several references that support related Books, Journals, Articles and so on. The results of this study indicate that the concept of Islamic Wasthiyyah in terms of several interpretive perspectives can be said as a sociological concept of Islam that emphasizes aspects universally related to the context of harmonious religious life, tolerance, and forming a moderate Islam in order to eliminate the extreme attitudes that have been many addressed to Islam.